Key Comparison Study - Organic Solvent Calibration Solution - Gravimetric preparation and value assignment of patulin (PAT) in acetonitrile (ACN) with 0.1 % formic acid (FA) - Josephs, R D; Bedu, M; Daireaux, A; Li, Xianjiang; Guo, Z; Li, Xiuqin; Zhang, Q; Gao, Y; Choteau, T; Martos, G; Westwood, S; Wielgosz, R I; et al. (IOP Publishing, 2023)
Main text The CCQM-K154.d comparison was coordinated by the the Bureau International des Poids et Mesures (BIPM) and the Chinese National Institute of Metrology (NIM) on behalf of the Organic Analysis Working Group (OAWG) of the Comité Consultatif pour la Quantité de Matière (CCQM) for National Measurement Institutes (NMIs) and Designated Institutes (DIs) which provide measurement services in organic analysis under the 'Comité International des Poids et Mesures' Mutual Recognition Arrangement (CIPM MRA) and/or have participated in the BIPM's Mycotoxin Metrology Capacity Building and Knowledge Transfer (MMCBKT) project as part of its "Metrology for Safe Food and Feed in Developing Economies" Capacity Building Programme. Gravimetrically-prepared solutions having an assigned mass fraction of specified organic analytes are routinely used to calibrate measurement processes for the quantification of the same analytes in matrix samples. Appropriate assignments of the property value and associated uncertainty of calibration solutions thus underpin the traceability of routine analysis and are critical for accurate measurements. Evidence of successful participation in relevant international comparisons is needed to document calibration and measurement capability claims (CMCs) made by national metrology institutes and designated institutes. In total, twelve NMIs/DIs participated in the Track C, Model II, Key Comparison CCQM-K154.d [Gravimetric preparation and value assignment of patulin (PAT) in acetonitrile (ACN) with 0.1 % formic acid (FA)] for emerging areas of global interest and innovation. Participants were requested to gravimetrically prepare calibration solutions and value assign the mass fractions, expressed in mg/kg, of PAT in ACN with 0.1 % FA solution. Study samples, with assigned values and associated uncertainties were prepared by the comparison participants and sent to the coordinating laboratory for comparison. The Key Comparison Reference Values (KCRVs), calculated form values measured by the coordinating laboratory based on calibrations obtained from independent gravimetrically prepared calibrant solutions, agreed with participants reported values, within their stated uncertainties. PAT is a mycotoxin produced by a variety of moulds, particularly by fungi of the genus Aspergillus and Penicillium. Often found in rotting apples and apple products, PAT can also occur in various other moldy fruits, grains and foods. Major human dietary sources of PAT are apples and apple juice made from affected fruit. PAT is relatively stable when given a short-acting heat-treatment, especially in an acidic environment. It was anticipated to provide a challenge representative for the gravimetrical preparation and value assignment of PAT calibration solutions in the mass fraction range of 10 mg/kg to 100 mg/kg of mycotoxins with broadly similar structural characteristics. Eight participants of the MMCBKT programme were provided with a stock solution having a known PAT mass fraction and expanded uncertainty to use to gravimetrically prepare and value assign a calibration solution. Two NMIs/DIs used reference materials for preparing their solutions while five NMIs/DIs participated using their own calibration solutions. The use of in-house solutions required an additional capacity to undertake a fit-for-purpose purity assessment. NIM was the only NMI participating using both the MMCBKT based and their own in-house assigned solutions in order to connect the two different groups. It was decided to propose separate KCRVs for each of the two ampoules provided by the participating NMIs/DIs based on the PAT mass fraction. This allowed participants to demonstrate the efficacy of their implementation of the approaches used to gravimetrically prepare calibration solutions and to assess the PAT mass fraction. The majority of the PAT mass fraction KCRVs (wKCRV) for CCQM-K154.d spanned a mass fraction range of 9.72 mg/kg to 63.40 mg/kg. The relative expanded uncertainties U(wKCRV) ranged from 2.0 % to 5.4 %. Inspection of the degree of equivalence plots for the PAT mass fraction assignments in CCQM-K154.d indicated that there was an excellent agreement of results. To reach the main text of this paper, click on Final Report. Note that this text is that which appears in Appendix B of the BIPM key comparison database https://www.bipm.org/kcdb/. The final report has been peer-reviewed and approved for publication by the CCQM, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).